Implementation of Cooperative Learning Methods in Fiqh Subjects to Build Students' Critical Thinking at SMP Muhammadiyah 1 Gamping - Akbar Prayogi Putra Suprapto; Tumin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This research aims to explore the implementation of the Cooperative Learning method in Fiqh learning and how its implementation can shape the critical thinking of students at SMP Muhammadiyah 1 Gamping. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The research subjects consisted of two Fiqh teachers and three students in grades 2 and 3. The results of the study show that the Cooperative Learning method is effective in increasing students' active participation, analytical skills, argumentation, and understanding of Fiqh materials. Strategies such as small group formation, discussions, presentations between groups, and the use of jigsaw and brainstorming approaches have been proven to encourage students to think critically. Despite obstacles such as differences in individual abilities and material characteristics, these were successfully overcome through a differential approach and the role of the teacher as a facilitator. The findings suggest that the implementation of cooperative learning methods significantly enhances both understanding of Fiqh material and the development of critical and collaborative thinking, aligning with the demands of 21st-century learning. This study contributes to the pedagogical approach in Islamic education, particularly in fostering critical thinking and collaboration among students.